These old shades - Heyer, Georgette, 1902-1974. (London : Arrow Books, 2004)
Justin Alastair, the Duke of Avon, finds his single-minded pursuit of revenge against the Comte de St. Vire sidetracked by a beautiful orphan.
Originally published in 1926.
Adult.
Adult
Keywords: Illegitimate children -- Fiction; Historical fiction; Illegitimacy -- Fiction; Love stories; England -- Social life and customs -- 18th century -- Fiction; England -- Social life and customs -- Fiction; Historical fiction; Love stories